Hereditariedade da cor das vagens de Phaseolus vulgaris L - II - Floriano de Moraes, Carlos; Vieira, Clibas (Revista Ceres, 2025)
In the present study, seven varieties of common beans (Phaseolus vulgaris L.) were used: ''Rico 23'' and ''Chimbolo 233'' both with dark pink pods and violet flowers; ''Preto 146'', with dark purple pods and violet flowers; ''Pardo 90'', with red pods and pink flowers; ''Manteigio Preto 20'' and ''Baetio Manteiga-41'', both with striped pods and violet flowers; ''Manteigao Fosco 11'', with yellow pods and white flowers. The pod colors were observed immediately before they began to ripen. Thus, the variety ''Manteigao Fosco 1I'' is not considered a wax bean since its pods are green and only change to yellow at maturity.